Komik Online “Ngopi, Yuk!”: Kajian Praanggapan dalam Perspektif Pragmatik - Bambang Eko Hari Cahyono; Arifah Putri Nur Nadila (Badan Pengembangan dan Pembinaan Bahasa, 2024)
The scope of pragmatic studies consists of 3 components, namely presupposition, conversational implicature, and entailment. One of the pragmatic studies that examines the meaning of assumptions or assumptions in speaking is presupposition. This study aims to describe and explain the dominant forms of presupposition in the online comic